Memahami Metode Warga Gereja Sebagai Kaum Awam Dalam Sejarah Dan Masa Kini (International Forum of Researchers and Lecturers, 2024)
In writing this article, the author examines the role of the laity in the church, highlighting the development of their participation methods over time. The laity, as non-clergy members, contributed to the mission of the church and the spread of the gospel. From an active role in the early church, they experienced a transformation in the middle ages, but the protestant reformation restored their involvement through the concept of the